Economic analysis of environmental impacts for the appraisal decision of ODA projects - KIM, Kihwan (KDI School, 2018)
This research aims to check that how valuation of socio-environmental impacts in a cost-benefit analysis (CBA) affects the investment decision of official development assistance (ODA) project. A dam construction project gives significant impacts to the surrounding sites. The assessment of the impacts is important because it can save potential ex-post costs to prevent any opposition and enhance aid effectiveness from the incurred overrunning costs of large dam projects. With conventional CBA for direct costs and benefits, indirect impacts such as biodiversity losses are quantified by revealed references and inserted into the CBA. The alternative case is analyzed if it deserves to be invested, and compared with the original case. Together sensitivity analyses are performed with NPV, B/C Ratio, and EIRR. As a result, both of the cases indicate that the project is economically feasible. Although environmental costs reduce the net benefit, the sales benefit is strong enough to promote the project, which is sensitive to the benefit. If all the indirect variables are additionally valuated in the CBA and incorporated with other methods including the environmental impact assessment (EIA), the project decision could be made more accurately. Now it is inevitable to apply the adjusted CBA to fully understand the reality.
Thesis(Master) --KDI School:Master of Development Policy,2018